A note on the occurrence of Cyrtopodium paludicolum Hoehne (Cyrtopodiinae) in the Diamantino Plateau, Minas Gerais, Brazil (Revista Espinhaço, 2023)
The genus Cyrtopodium comprises species that can exhibit epiphytic, rupicolous, and terrestrial habits. Although they have a wide distribution in the state of Minas Gerais, the occurrence of Cyrtopodium paludicolum Hoehne was unknown in the Diamantino Plateau, specifically in the municipality of Diamantina, until it was confirmed through field collections. This manuscript aims to present a note on this species’ new occurrence. The two fertile specimens found were collected in March, herborized, and deposited in Jeanine Felfili Dendrological Herbarium (HDJF) and Diamantina Herbarium (DIAM) of the Federal University of Jequitinhonha and Mucuri Valleys (UFVJM). We here present a picture of the species in its habitat, a map showing the location of its new sighting, its description, and a plate depicting its floral segments. This finding is significant for redefining the species' distribution range, especially because it has been frequently targeted by local orchid collectors.
Keywords: Rupestrian grasslands; Orchidaceae; Wetlands